Hospital admission and discharge: lessons learned from a large programme in southwest Germany - Forstner, Johanna; Pilz, Maximilian; Straßner, Cornelia; Weis, Aline; Litke, Nicola; Uhlmann, Lorenz; Peters-Klimm, Frank; Aluttis, Frank; Baldauf, Annika; Kiel, Marion; Qreini, Markus; Kaufmann-Kolle, Petra; et al. (International journal of integrated care, 2023)
Introduction: In the context of a GP-based care programme, we implemented an admission, discharge and follow-up programme.Description: The VESPEERA programme consists of three sets of components: pre-admission interventions, in-hospital interventions and post-discharge interventions. It was aimed at all patients with a hospital stay participating in the GP-based care programme and was implemented in 7 hospitals and 72 general practices in southwest Germany using a range of strategies. Its’ effectiveness was evaluated using readmissions within 90 days after discharge as primary outcome. Questionnaires with staff were used to explore the implementation process.Discussion: A statistically significant effect was not found, but the effect size was similar to other interventions. Intervention fidelity was low and contextual factors affecting the implementation, amongst others, were available resources, external requirements such as legal regulations and networking between care providers. Lessons learned were derived that can aid to inform future political or scientific initiatives. Conclusion: Structured information transfer at hospital admission and discharge makes sense but the added value in the context of a GP-based programme seems modest. Primary care teams should be involved in pre- and post-hospital care.